Tectonic style and evolution of the South Atlas Front (Western Sahara Atlas, Beni Ounif, Algeria): Insights from field investigation, geological mapping and structural analysis - Djeddi, Rabah; Bettahar, Abdellah; Serkhane, Ahmed; Rezig, Sabrina (Journal of African earth sciences (1994), 2025)
The Atlas Mountains constitute a fold-thrust belt resulting from the inversion of a rifted basin that developed in the southern margin of the Tethys. The closure of this basin remains a matter of debate, especially in terms of tectonic regime and structural style, whether it is characterized by thin-skinned or thick-skinned tectonics. The compression regime and oblique tectonics resulting from tectonic inversion have been subjects of discussion. Moreover, in the High Atlas, exhumation and salt tectonics have been a point of emphasis. A field study, accompanied by detailed geologic mapping and structural analysis of South Atlas Front (SAF), aimed to highlight the geodynamic evolution of the southwestern part of the Atlas. The findings, presented through cross-sections and results, demonstrate the presence of both transpressive and compressive regimes. The integration of salt tectonics and the development of mini basins between ridges created from salt migration and diapir rise above the normal fault related to rifting episodes has been interpreted. The transpression is characterized by dextral strike-slip faulting of the South Atlas Front. The compressional tectonic regime is marked by a major north-east transverse sinistral strike-slip fault and the development of thrust and back-thrust systems in the South Atlas Front. This structural architecture of the SAF is governed by a thick-skinned tectonic style (deep seated basement faults) with salt tectonic activity since Early Jurassic. •Detailed geologic mapping and structural analysis of South Atlas Front (SAF).•Transpressive faulting of the South Atlas Front, Beni Ounif, Algeria.•Beni Ounif Major sinistral strike-slip fault.•Geodynamic evolution of the South-Western part of Atlas fold-thrust belt.•A new interpretation of the mini-basins and the fold-thrust belt in relation to salt tectonics.